REVIEW ON SOME MEDICINAL FLOWERS USEFUL IN SKIN DISORDERS W.S.R. TO ANTI-BACTERIAL ACTIVITY - *Dodke Pranita; Pansare Tabassum; Borokar Archana (International Journal of Ayurveda and Pharma Research, 2017)
Skin diseases are numerous and a frequently occurring health problem affecting all ages from the neonates to the elderly and cause harm in number of ways. It is not a life threatening disorder, but the sign and symptoms like itching, burning, oozing make the patients irritating and worried. Infection of the skin due to Staphylococcus aureus is a challenge for the physicians. S. aureus is spherical gram-positive bacteria, which is immobile and forms grape-like clusters. It is a normal inhabitant of the skin and mucous membranes in the nose of a healthy human. The speciality of S. aureus is that it is infectious to both animals and humans and survives only on dry skin. It can be spread through contaminated surfaces, through the air and through people. Modern medicine has limitations for the treatment of such skin disease. But in Ayurveda, many references can be found in classical texts, about successful treatment of various skin diseases like Kandu, Pama etc. In this article we have reviewed, the most useful five herbs from the Pushpa varga of Bhavprakasha Nighantu. Many scholars have experimentally studied the antibacterial activity of these flowers in details. We have tried to explain the anti bacterial activity of flowers from these herbs in accordance with Ayurvedic concept.